Testing and simulation of a bolted and bonded joint between steel deck and composite side shell plating of a naval vessel. (1st October 2018) - Gaiotti, Marco; Ravina, Enrico; Rizzo, Cesare M.; Ungaro, Andrea
Highlights: Large scale collapse testing of a steel-composite joint, both bolted and bonded, was carried out. Analytical simplified and finite element models were developed to assess its structural behavior. A significant scale effect has been noted between numerical simulations and large-scale test. Noticeably, structural analyses were carried out without test results available, as usual in design practice. Various reasons were identified to explain deviations of structural models from reality. Abstract: This paper describes the large-scale testing and the finite element simulations of the collapse of a steel-composite joint, both bolted and bonded. The joined structures are typical ones of shipbuilding and namely of naval ships. Composite superstructures, beside a valuable weight reduction, may improve the signature features of the ship by embedding installed electronic devices into a composite mast. In the frame of a broader research project, including the electromagnetic characterization of the composite structures, also the structural design and its optimization were exploited, embracing, among other issues, the joining solutions between the steel deck structures to the composite ones of the superstructure side shell. A large-scale specimen of the joint was conceived and collapse tested while, in parallel, design simulations were carried out at different levels of detail. Eventually, a complete description of the collapse of the joint, including the nonlinear simulation by finite element analysis of the progressive failure of the composite laminates of the side shell was obtained and test results were used to validate the numerical models. Depending on the design stage, various scantling procedures, from a very simplified one to a rather complex and time-consuming numerical analysis, can now be applied to verify the structural behavior of these steel to composite joints as well as to select the most cost-effective solution among several options.